Monometallic Pd and Pt and Bimetallic Pd-Pt/Al2O3-TiO2 for the HDS of DBT: Effect of the Pd and Pt Incorporation Method - Reynaldo Martínez Guerrero; Agileo Hernández-Gordillo; Víctor Santes; Jorge Roberto Vargas García; José Escobar; Leonardo Díaz-García; Lucía Díaz Barriga Arceo; Vicente Garibay Febles (Journal of Chemistry)
The effect of the preparation method of monometallic Pd and Pt and bimetallic Pd-Pt/Al2O3-TiO2 catalysts on the hydrodesulfurization (HDS) of dibenzothiophene (DBT) was investigated in this study. The synthesis was accomplished using three methods: (A) impregnation, (B) metal organic chemical vapor deposition (MOCVD), and (C) impregnation-MOCVD. The bimetallic Pd-Pt catalyst prepared by the impregnation-MOCVD method was most active for the HDS of DBT compared to those prepared by the single impregnation or MOCVD method due to the synergetic effect between both noble metals. The greater selectivity toward biphenyl indicated that this bimetallic Pd-Pt catalyst preferentially removes sulfur via the direct desulfurization mechanism. However, the bimetallic Pd-Pt catalyst prepared using the single MOCVD method did not produce any cyclohexylbenzene, which is most likely associated with the hydrogenation/dehydrogenation sites.